Experimental Investigation of a Laser Wireless Video Communication System Using Intensity Modulated /Direct Detection Technique - Kbashi, Hani J. (Iraqi Journal of Laser, 2010)
In this work Laser wireless video communication system using intensity modualtion directdetection IM/DD over a 1 km range between transmitter and receiver is experimentally investigated anddemonstrated. Beam expander and beam collimeter were implemented to collimete laser beam at thetransmitter and focus this beam at the receiver respectively. The results show that IM/DD communicationsysatem using laser diode is quite attractive for transmitting video signal. In this work signal to noiseratio (S/N) higher than 20 dB is achieved in this work.